Strategi Meningkatkan Literasi Anak Melalui Kegiatan Membaca Nyaring dalam Program KKN Tematik Literasi di Kampung Bandar Pedada, Siak - Zulkarnain, Zulkarnain; Nasution, Nasry El Padly; Sinaga, Sri Deviana; Emanuela, Bianca; Shilfiani, Shelly; Tafrikhan, Tafrikhan; Fadhillah, Muhammad Nabil; Naim, Candra Abshar; Hutabalian, Fernandito Abednego; Saputra, Bayu; Anggraini, Desti; Hasibuan, Rahayu Bulan; Nabila, Raizha Shafiah (Unri Conference Series: Community Engagement, 2025)
Reading interestis onc of the important aspects in children's literacy development This activity is motivated by the low reading habits of children by applying strategies through reading aloud activities at to increase children's interest in reading. The activity was carried out in Bandar Pedada Village, Sabak Auh District, Siak Regency on June 23, 2025 to August 1, 2025. The mcthod used was a mixed approach, namely qualitative and quantitative. Qualitativc data was obtained through direct obscrvation and documentation during the activity. Meanwhilc, quantitative data was obtained through giving pretest andgosttest to 20 children before and after participating in reading aloud activities by conducting paired sample t-test approach. The pretest results showed an average score of 36.55, while the posttest score increased to 46.50. The paired sample t-test produced a significance value of 0.000 (p < 0.05), which means thereis asignificant increase in scores after the activity is carried out. These results show that reading aloud activities have a positive influence on inereasing children's interest and litcracy skills. In addition, children were more active, enthusiastic and showed a higher intcrest in books during the process. Thus, reading aloud activities are effective as a strategy to improve children's literacy in the village, The program also supports the strengthening of reading culture in the community through a fin and interactive approach.